1987
DOI: 10.1248/cpb.35.1427
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the constituents of umbelliferae plants. XV Constituents of Cnidium officinale : Occurrence of pregnenolone, coniferylferulate and hydroxyphthalides.

Abstract: Pregnenolone (1), coniferylferulate (2) and nine mono-and dihydroxyphthalide derivatives (5-13) were isolated from the commercial C. officinale rhizome. Their structures were determined from the spectroscopic data and the dihydroxyphthalides senkyunolide-H (11) and-1 (12) and senkyunolide-J (13) were synthesized from the major components ligustilide (14) and senkyunolide-A (16), respectively. These oxygenated phthalides were absent in the fresh C. officinale rhizome and they were shown to be derived from the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 9 publications
2
30
0
Order By: Relevance
“…3, percentages of the unchanged compounds and their corresponding degradation products were calculated based on 1 : 1 stoichiometric con- The results were in good agreement with previous reports in that 5 could be hydrolyzed to 1 under various conditions including high temperature. [15][16][17] In the case of compound 6, significant degradation occurred under both conditions although very low recovery was obtained. Different degradation products were identified under different conditions.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…3, percentages of the unchanged compounds and their corresponding degradation products were calculated based on 1 : 1 stoichiometric con- The results were in good agreement with previous reports in that 5 could be hydrolyzed to 1 under various conditions including high temperature. [15][16][17] In the case of compound 6, significant degradation occurred under both conditions although very low recovery was obtained. Different degradation products were identified under different conditions.…”
Section: Resultsmentioning
confidence: 97%
“…13) On the other hand, sun-drying or heating in oven are the most common and traditional ways for drying Chuanxiong. It has been reported that some of the constituents in Chuanxiong, e.g., 4, 5 and 6 are photo-and/or thermo-labile, [14][15][16][17][18] although data about the influence of post-harvest drying and processing on chemical profiles of Chuanxiong are unavailable. With unavailability of detailed processing information on commercial samples, our preliminary evaluation of ten purchased Chuanxiong herbs, which were processed differently, demonstrated significant variations in chemical profiles (Fig.…”
mentioning
confidence: 99%
“…Nevertheless, these variations were still considered to be adequate, because reproducible extraction of these less lipophilic components by SCFE was recognized difficult in general [24]. Furthermore, compounds 3 and 4 were the minor ingredients in Chuanxiong herb and were reported not as the major components contributing to the therapeutic outcomes of Chuanxiong [32,33]. Therefore, the overall extraction reproducibility for the developed SCFE condition was considered to be adequate for the extraction of all main ingredients in Chuanxiong herb.…”
Section: Reproducibility Of the Selected Scfe Conditionmentioning
confidence: 99%
“…The number of cultured SMC was count ed with a hemocytometer every 12 hr from the first to the 11th day in culture. Table 1 (3,9,10). All phthalides were dis solved in 100% ethanol and then diluted with 10% FBS DMEM to the final concentration (0.0507o ethanol).…”
Section: Assay Of Smc Proliferationmentioning
confidence: 99%